Sight-dependent quality of life and ophthalmic findings in a group of Brazilian patients with multiple sclerosis - Yára Dadalti Fragoso; Ricardo Menon Nosé; Regina Aidar Menon Nosé; Walton Nosé; Simone Vieira; Alessandro Finkelsztejn (Arquivos de Neuro-Psiquiatria, 2011)
OBJECTIVE: To assess the visual quality of life in patients with multiple sclerosis (MS), and to observe whether this parameter could be correlated to the findings of the ophthalmologic examination. METHOD: The translated and validated 25-Item National Eye Institute Visual Function Questionnaire (VFQ-25) was used to assess the visual quality of life. Clinical data on MS, visual acuity, visual fields, optic coherence tomography (OCT) and disc cupping were used for assessing correlation with VFQ-25. RESULTS: The mean VFQ-25 value was 78.6±18.2% in 27 patients. VFQ-25 did not correlate with patients' ages, with disability (EDSS), disease duration or medication use. Visual acuity showed a relatively poor (<60%) correlation to VFQ-25, while no correlation could be established between visual fields, OCT and disc cupping with VFQ-25. CONCLUSION: MS patients present several alterations in their eyes and sight that cannot be assessed by isolated measures. Ophthalmological examination of these patients must include many parameters not usually used in standard ophthalmologic consultations.